A remarkable Newportia from the Colombian Andes, with the proposition of a new subgenus (Scolopendromorpha, Scolopocryptopidae, Newportiinae) - Tulande-M, Esteban; Prado, César Camilo; Jiménez, Sebastián Galvis; Chagas-Jr, Amazonas (Zootaxa, 2020)
A new monotypic subgenus Newportia (Andeocryptops) subgen. n is described based on 18 specimens of N. (A.) shelleyi sp. n. This form is endemic to the Colombian Andes showing the following unique combination of morphological features: very short and thin, a cylindrical and not segmented ultimate tarsus 2, a “spinning-spur” (see below) on the ultimate tarsus 1, short paramedian sutures close to the anterior and posterior margins of cephalic plate, a tibial lateral spur and a glandular pore fields in the ultimate femur. An identification key to the Newportia subgenera, as well as a key to the Ectonocryptops, Ectonocryptoides and Andeocryptops species are included.